The ancient magus' bride. Volume 5 - Yamazaki, Kore; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2016)
"Chise has taken great strides in overcoming her dark past, and is ready for a brighter future at Ella's side. As for the magus himself, he is finally able to put a name to the strange emotion he's been feeling for Chise. Meanwhile, a deadly threat looms. When a panicked fairy appears at Chise's bedside, begging for help, is there anything the young, novice mage can do...?" -- Page [4] of cover.